Kikuchi-Fujimoto disease as the initial manifestation of systemic lupus erythematosus complicated with macrophage activation syndrome: two case reports and a review of literature - Chenxi Liu; Yingying Jin; Hua Huang; Fei Ding; Zhen Yang; Xuemei Xu; Shengfang Bao; Jing Ma; Yanliang Jin (BMC, 2022)
Abstract Background Kikuchi-Fujimoto disease (KFD) is a self-limiting and benign disease characterized by cervical lymphadenopathy and fever. Although KFD should be made differentially diagnosed from infectious, autoimmune, and malignant diseases, it sometimes occurs in patients with systemic lupus erythematosus (SLE) and can be complicated with macrophage activation syndrome (MAS). However, it is rare that KFD is the initial manifestation of SLE and to be complicated with MAS. Case presentation A 9.6-year-old girl presented with high-grade fever, double-side cervical lymphadenopathy with mild pain of one week, leukopenia, alopecia, and rash on the cheek. During hospitalization, laboratory investigations showed positive antinuclear antibody (ANA), low complement 3 (C3), and low complement 4 (C4). Imaging investigations showed pleural and pericardial effusion. A 10.3-year-old girl presented with intermittent high-grade fever, double-sided cervical lymphadenopathy with obvious pain of 1-month duration, and discoid lesion on the cheek. During hospitalization, laboratory investigations showed positive ANA, leukopenia, thrombocytopenia, anemia with positive Coombs' test, low C3, and positive Smith antibodies. Both cases were diagnosed with KFD using lymph node biopsy, simultaneously fulfilling the diagnostic criteria of SLE. Subsequently, the two girls became complicated with MAS, followed by interstitial lung disease and neuropsychiatric lupus, respectively. Both patients benefited from high-dose methylprednisolone pulse therapy combined with intravenous cyclophosphamide. Conclusions More attention should be paid to differential diagnosis, especially SLE, in children diagnosed with KFD. In addition, children with SLE who presented with KFD as the initial manifestation seem to have a higher risk of developing MAS and experiencing organ involvement.